Comparative evaluation of propofol or etomidate induction in dexmedetomidine- glycopyrrolate- butorphanol premedicated brachycephalic dogs - Sharma, Deepti; Bhalru, Ribha; Kumar, Adarsh; Ankita; Kumar, Amit; Bodh, Deepti; Tyagi, S.P.; Kumar, Rohit (Indian Journal of Veterinary Surgery, 2026)
This study evaluated and compared the induction characteristics of propofol and etomidate in 20 brachycephalic dogs undergoing various surgical procedures and premedicated with dexmedetomidine, glycopyrrolate, and butorphanol. The dogs were randomly divided into two groups of 10 animals each: group P (propofol) and group E (etomidate). All animals were preanaesthetized with dexmedetomidine (5 µg/kg body weight), glycopyrrolate (0.01 mg/kg), and butorphanol (0.2 mg/kg) administered intramuscularly in a single syringe, followed by preoxygenation. Induction was achieved intravenously to effect using propofol in group P and etomidate in group E. Anaesthesia was maintained with isoflurane in 100% oxygen. The mean induction doses of propofol and etomidate were 1.80±0.81 mg/kg and 0.72±0.50 mg/kg, respectively. Intubation was more smoothly facilitated in group P. Group P also exhibited a more pronounced reduction in blood pressure and heart rate, although values remained within physiological limits. Recovery was faster in group E, with earlier return of palpebral reflex, head lifting, and sternal recumbency. Etomidate demonstrated superior cardiovascular stability and recovery quality, indicating that it may be the preferred induction agent in brachycephalic dogs to optimize anaesthetic safety and outcomes.